Association between body roundness index and advanced cardiovascular-kidney-metabolic syndrome - Chen, Yuehui; Tu, Hongxiang; Liang, Min; Shen, Mo (Frontiers in Nutrition, 2025)
BackgroundCardiovascular–kidney–metabolic (CKM) syndrome is a disease characterized by interrelated cardiovascular, renal, and metabolic abnormalities. The body roundness index (BRI) is an innovative anthropometric index that characterizes human body shape by calculating body roundness and using eccentricity to estimate visceral and total body fat percentages. The present study aimed to clarify the relation between BRI and advanced CKM syndrome.MethodsData were obtained from the National Health and Nutrition Examination Survey conducted between 2005 and 2018. Tertiles based on data analysis were applied to divide the levels of BRI. Regression methods assessed the association of BRI with the risk of advanced CKM syndrome. Moreover, receiver operating characteristic analysis determined BRI’s predictive performance for such a syndrome.ResultsThe present study included 12,329 participants, with an advanced CKM occurrence rate of 12.20%. Regression analysis revealed a positive association between BRI and advanced CKM syndrome. After adjusting for covariates, individuals in the highest BRI tertile (T3) showed a significantly higher prevalence of advanced CKM syndrome compared to the reference group (odds ratio: 1.49; 95% confidence interval: 1.09–2.03, p < 0.001). Smoothed curve-fitting analyses showed a linear trend. Subgroup analyses yielded results consistent with the total results. Furthermore, restricted cubic spline analyses indicated that BRI was a stronger predictor of advanced CKM syndrome than other anthropometric measures.ConclusionAn increased BRI is associated with a higher occurrence rate of advanced CKM syndrome. BRI demonstrated a stronger correlation with advanced CKM than traditional measures and warrants consideration as a preferred metric for CKM risk stratification.